PIC16F1847 microcontroller-based programmable logic controller : hardware and basic concepts - Uzam, Murat, 1968- (Boca Raton, FL : CRC Press, 2021)
Programmable logic controllers (PLCs) have been used extensively and are offered in terms of functions, program memories, and the number of inputs/outputs (I/Os), ranging from a few to thousands. With a focus on how to design and implement a PLC, this volume explains hardware and associated basic concepts of PLC. Authors have used PIC16F1847 microcontroller with: 8192 words of Flash program memory, 1024 bytes of SRAM data memory, 256 bytes of EEPROM data memory, the maximum operating speed of 32 MHz, 16-level deep hardware stack, an enhanced instruction set consisting of 49 single-word instructions. Flowcharts are provided to help the understanding of macros (instructions). Aimed at researchers and graduate students in electrical engineering, power electronics, robotics and automation, sensors, this book: Explains how to design and use a PIC16F1847 microcontroller-based PLC. Provides easy to use software structures written by using the PIC Assembly programming language. Describes a PLC from a designer's perspective. Explains the basic hardware and basic software structures of the PIC16F1847 based PLC. Focuses on concepts like Contact and Relay Based Macros, Flip-Flop Macros, Timer Macros, Counter Macros and Comparison Macros.
Chapter 1 -- Hardware of the PIC16F1847-Based PLC Chapter 2 -- Basic Software 2.1. Definition and Allocation of Variables 2.2. Contents of the File PICPLC-PIC16F1847-memory.inc 2.3. Contents of the File PICPLC-PIC16F1847-main.asm 2.4. Contents of the File PICPLC-PIC16F1847-user.inc 2.5. Contents of the File PICPLC-PIC16F1847-subr.inc 2.6. Contents of the File PICPLC-PIC16F1847-macros.inc 2.7. Example Programs 2.8. Reference Chapter 3 -- Contact and Relay Based Macros 3.1. Macro "ld" (load) 3.2. Macro "ld-not" (load-not) 3.3. Macro "not" 3.4. Macro "or" 3.5. Macro "or-not" 3.6. Macro "nor" 3.7. Macro "and" 3.8. Macro "and -not" 3.9. Macro "nand" 3.10. Macro "xor" 3.11. Macro "xor-not" 3.12. Macro "xnor" 3.13. Macro "out" 3.14. Macro "out-not" 3.15. Macro "mid-out" (Midline Output) 3.16. Macro "mid-out-not" (Inverted Midline Output) 3.17. Macro "in-out" 3.18. Macro "inv-out" 3.19. Macro "-set" 3.20. Macro "-reset" 3.21. Macro "SR" (Set-Reset) 3.22. Macro "RS" (Reset-Set) 3.23. Macro "r-edge" (rising edge detector) 3.24. Macro "f-edge" (falling edge detector) 3.25. Macro "r-toggle" (Output Toggle with Rising Edge Detector) 3.26. Macro "f-toggle" (Output Toggle with Falling Edge Detector) 3.27. Macro "adrs-re" (Address Rising Edge Detector) 3.28. Macro "adrs-fe" (Address Falling Edge Detector) 3.29. Macro "setBF" (set Bit Field) 3.30. Macro "resetBF" (reset Bit Field) 3.31. Examples for Contact and Relay Based Macros Chapter 4 -- Flip-Flop Macros 4.1. Macro latch1 (D latch with active high enable) 4.2. Macro latch0 (D latch with active low enable) 4.3. Macro "dff-r" (rising edge triggered D flip-flop) 4.4. Macro dff-r-SR (rising edge triggered D flip-flop with active high preset (S) and clear (R) inputs) 4.5. Macro "dff-f" (falling edge triggered D flip-flop) 4.6. Macro dff-f-SR (falling edge triggered D flip-flop with active high preset (S) and clear (R) inputs) 4.7. Macro "tff-r" (rising edge triggered T flip-flop) 4.8. Macro tff-r-SR (rising edge triggered T flip-flop with active high preset (S) and clear (R) inputs) 4.9. Macro "tff-f" (falling edge triggered T flip-flop) 4.10. Macro tff-f-SR (falling edge triggered T flip-flop with active high preset (S) and clear (R) inputs) 4.11. Macro "jkff-r" (rising edge triggered JK flip-flop) 4.12. Macro jkff-r-SR (rising edge triggered JK flip-flop with active high preset (S) and clear (R) inputs) 4.13. Macro "jkff-f" (falling edge triggered JK flip-flop) 4.14. Macro jkff-f-SR (falling edge triggered JK flip-flop with active high preset (S) and clear (R) inputs) 4.15. Examples for Flip-Flop Macros Chapter 5 -- Timer Macros 5.1. On Delay Timer (TON) 5.2. Macro "TON-8" (8-Bit ON Delay Timer) 5.3. Macro "TON-16" (16-Bit ON Delay Timer) 5.4. Retentive On Delay Timer (RTO) 5.5. Macro "RTO-8" (8-Bit Retentive ON Delay Timer) 5.6. Macro "RTO-16" (16-Bit Retentive ON Delay Timer) 5.7. Off Delay Timer (TOF) 5.8. Macro "TOF-8" (8-Bit OFF Delay Timer) 5.9. Macro "TOF-16" (16-Bit OFF Delay Timer) 5.10. Pulse Timer (TP) 5.11. Macro "TP-8" (8-Bit Pulse Timer) 5.12. Macro "TP-16" (16-Bit Pulse Timer) 5.13. Extended Pulse Timer (TEP) 5.14. Macro "TEP-8" (8-Bit Extended Pulse Timer) 5.15. Macro "TEP-16" (16-Bit Extended Pulse Timer) 5.16. Oscillator Timer (TOS) 5.17. Macro "TOS-8" (8-Bit Oscillator Timer) 5.18. Macro "TOS-16" (16-Bit Oscillator Timer) 5.19. Examples for Timer Macros Chapter 6 -- Counter Macros 6.1. Up Counter (CTU) 6.2. Macro "CTU-8" (8-Bit Up Counter) 6.3. Macro "CTU-16" (16-Bit Up Counter) 6.4. Down Counter (CTD) 6.5. Macro "CTD-8" (8-Bit Down Counter) 6.6. Macro "CTD-16" (16-Bit Down Counter) 6.7. Up/Down Counter (CTUD) 6.8. Macro CTUD-8" (8-Bit Up/Down Counter) 6.9. Macro CTUD-16" (16-Bit Up/Down Counter) 6.10. Generalized Up/Down Counter (GCTUD) 6.11. Macro GCTUD-8" (8-Bit Generalized Up/Down Counter) 6.12. Macro GCTUD-16" (16-Bit Generalized Up/Down Counter) 6.13. Examples for Counter Macros Chapter 7 -- Comparison Macros (Available as E-Ancillaries) 7.1. Macro "R1-GT-R2" 7.2. Macro "R1-GT-R2-16" 7.3. Macro "R1-GE-R2" 7.4. Macro "R1-GE-R2-16" 7.5. Macro "R1-EQ-R2" 7.6. Macro "R1-EQ-R2-16" 7.7. Macro "R1-LT-R2" 7.8. Macro "R1-LT-R2-16" 7.9. Macro "R1-LE-R2" 7.10. Macro "R1-LE-R2-16" 7.11. Macro "R1-NE-R2" 7.12. Macro "R1-NE-R2-16" 7.13. Macro "R-GT-K" 7.14. Macro "R-GT-K-16" 7.15. Macro "R-GE-K" 7.16. Macro "R-GE-K-16" 7.17. Macro "R-EQ-K" 7.18. Macro "R-EQ-K-16" 7.19. Macro "R-LT-K" 7.20. Macro "R-LT-K-16" 7.21. Macro "R-LE-K" 7.22. Macro "R-LE-K-16" 7.23. Macro "R-NE-K" 7.24. Macro "R-NE-K-16" 7.25. Macro "in-RANGE" 7.26. Macro "in-RANGE-16" 7.27. Macro "out-RANGE" 7.28. Macro "out-RANGE-16" 7.29. Macro "Hbit-CaC" (High Bit Count and Compare) 7.30. Macro "Lbit-CaC" (Low Bit Count and Compare) 7.31. Examples for Comparison Macros Appendix A -- List of Components for Boards and Modules (Available as E-Ancillaries) Table A.1. Some example universal double sided prototyping printed circuit boards (PCBs) that can be used for the modules developed in this book Table A.2. List of components for the PIC16F1847-Based PLC CPU board Table A.3. List of components for one I/O extension board only Table A.4. List of components for the 5.00V voltage reference module Table A.5. List of components for the RC low pass filter module Table A.6. List of components for the voltage regulator module
OCLC-licensed vendor bibliographic record.
Keywords: PIC microcontrollers; Programmable logic devices; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General; TECHNOLOGY / Electronics / Circuits / General